2011
DOI: 10.1002/glia.21224
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling in the cerebellum: Bergmann glial cells express functional ionotropic P2X7 receptors

Abstract: Astrocytes constitute active networks of intercommunicating cells that support the metabolism and the development of neurons and affect synaptic functions via multiple pathways. ATP is one of the major neurotransmitters mediating signaling between neurons and astrocytes. Potentially acting through both purinergic metabotropic P2Y receptors (P2YRs) and ionotropic P2X receptors (P2XRs), up until now ATP has only been shown to activate P2YRs in Bergmann cells, the radial glia of the cerebellar cortex that envelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
(104 reference statements)
2
9
0
Order By: Relevance
“…Evidence from the retina suggests that neuron-glia signaling may be mediated by neuronally released ATP acting on glial P2Y receptors rather than via activation of mGluRs by glutamate (Newman, 2005; Metea and Newman, 2006). Indeed, it has been shown that astrocyte [Ca 2+ ] i signals can be evoked by ATP in the cerebral cortex (Sun et al, 2013) and in cerebellar slices (Piet and Jahr, 2007; Habbas et al, 2011). Alternative hypotheses of astrocyte control of vessel diameter also include the efflux of K + through Ca 2+ -activated K + channels in astrocyte endfeet (Filosa et al, 2006), although the functional, in vivo , significance of this pathway remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the retina suggests that neuron-glia signaling may be mediated by neuronally released ATP acting on glial P2Y receptors rather than via activation of mGluRs by glutamate (Newman, 2005; Metea and Newman, 2006). Indeed, it has been shown that astrocyte [Ca 2+ ] i signals can be evoked by ATP in the cerebral cortex (Sun et al, 2013) and in cerebellar slices (Piet and Jahr, 2007; Habbas et al, 2011). Alternative hypotheses of astrocyte control of vessel diameter also include the efflux of K + through Ca 2+ -activated K + channels in astrocyte endfeet (Filosa et al, 2006), although the functional, in vivo , significance of this pathway remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of P2Y receptors (which are highly expressed in astrocyte endfeet: Simard et al, 2003), activates phospholipase C (PLC) and the downstream calcium-dependent signaling pathways discussed above (Figure 2). ATP can also act on glial P2X 7 receptors, resulting in an increase in astrocyte [Ca 2+ ] i (Carrasquero et al, 2009; Habbas et al, 2011) and triggering the formation and release of vasoactive substances (Figure 2). In addition to neuronally released ATP, calcium-dependent ATP exocytosis by glial cells may occur (Pangrsic et al, 2007; Blum et al, 2008).…”
Section: Alternative Mechanisms Of Astrocyte Control Of Cbfmentioning
confidence: 99%
“…2010). Cortical astrocytes and cerebellar Bergmann glial cells also express P2X 7 purinoceptors (Habbas et al. 2011; Oliveira et al.…”
Section: Ionotropic Receptors and Transporters Provide For Fast Neuromentioning
confidence: 99%
“…For example, it has been shown that in mature mice, mGluR5, which is usually expected to mediate astrocytic Ca 2+ responses to glutamate, is downregulated, suggesting that this coupling mechanism might be more relevant for the very young brain (Sun et al, ). Other evidence suggests that neuron–glia signaling may be mediated by neuronally released ATP acting on glial P2Y receptors rather than via activation of mGluRs by glutamate (Calcinaghi et al, ; Habbas et al, ; Nizar et al, ; Sun et al, ). Group I mGluRs and the ATP receptor P2Y1 are both G protein–coupled receptors associated with Gαq signaling that induces Ca 2+ release from internal stores by generating IP3.…”
Section: Neuroprotective Mechanisms In Astrocytesmentioning
confidence: 99%